The Influence of Ethical Philosophy on Teachers' Work Ethic - Muslihuddin Muslihuddin; Kautsar Eka Wardhana; Tri Wahyudi Ramdhan; Nora Repo (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This paper aims to investigate how much ethical philosophy influences a teacher's work ethic in an educational context. The focus of the study involves evaluating teachers' understanding of the principles of ethical philosophy relevant to their duties and responsibilities as educators. Research methods involve literature studies, surveys, interviews, and content analysis to gain a comprehensive understanding. The results of this study are expected to provide an overview of the extent to which teachers understand ethical values and how they are reflected in their daily practices. It is also expected to identify a direct influence between the understanding of ethical philosophy and the work ethic of teachers. Case studies and statistical analysis are used to gain deeper insight into implementing ethical values in teaching, student interaction, and decision-making. Through a better understanding of the relationship between ethical philosophy and teacher work ethic, this research can contribute to the educational literature and open the door to developing strategies or training programs that can strengthen the influence of ethical philosophy in shaping ethical and meaningful educational practices.